2014
DOI: 10.1371/journal.pone.0097697
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Inhibitor Rapamycin Synergizes with a Fatty Acid Synthase Inhibitor to Induce Cytotoxicity in ER/HER2-Positive Breast Cancer Cells

Abstract: Patients with ER/HER2-positive breast cancer have a poor prognosis and are less responsive to selective estrogen receptor modulators; this is presumably due to the crosstalk between ER and HER2. Fatty acid synthase (FASN) is essential for the survival and maintenance of the malignant phenotype of breast cancer cells. An intimate relationship exists between FASN, ER and HER2. We hypothesized that FASN may be the downstream effector underlying ER/HER2 crosstalk through the PI3K/AKT/mTOR pathway in ER/HER2-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Using non‐cancer cell models, however, both Porstmann and Duvel and their respective coworkers have convincingly shown that Akt‐mediated cell growth and enhanced lipogenesis does result from downstream activation of SREBP‐1c through the action of mTOR complex 1 (mTORC1), and that this is accompanied by nuclear translocation of the active SREBP1c fragment and the expected induction of mRNAs coding the lipogenic enzymes (Porstmann et al, ; Duvel et al, ). As anticipated from this signaling cascade, simultaneous inhibition of FASN with Cerulenin and mTOR signaling with rapamycin exerted a synergistic anticancer effect in Her2/neu‐expressing BC cells (Yan et al, ).…”
Section: Oncogenic Antigen 519mentioning
confidence: 98%
“…Using non‐cancer cell models, however, both Porstmann and Duvel and their respective coworkers have convincingly shown that Akt‐mediated cell growth and enhanced lipogenesis does result from downstream activation of SREBP‐1c through the action of mTOR complex 1 (mTORC1), and that this is accompanied by nuclear translocation of the active SREBP1c fragment and the expected induction of mRNAs coding the lipogenic enzymes (Porstmann et al, ; Duvel et al, ). As anticipated from this signaling cascade, simultaneous inhibition of FASN with Cerulenin and mTOR signaling with rapamycin exerted a synergistic anticancer effect in Her2/neu‐expressing BC cells (Yan et al, ).…”
Section: Oncogenic Antigen 519mentioning
confidence: 98%
“…Fatty acid metabolism is also being targeted in combination with mTOR inhibitors for cancer therapy. In pre-clinical studies of ER/HER2 positive breast cancer, cerulenin, a FASN inhibitor synergized with rapamycin to induce apoptosis and inhibit tumorigenesis [308]. FASN inhibition in ovarian cancer led to cell death, which involved a caspase 2 mechanism via the mTORC1 negative regulator REDD1 [309].…”
Section: Co-targeting Mtor and Metabolismmentioning
confidence: 99%
“…Inhibition of MAP kinase also decreases transcription from the FASN promoter and reduces FASN expression in MCF7 cells [63] . The mTOR inhibitor rapamycin may also inhibit FASN in breast cancer cells [64] . Recently, a "HER2-FASN axis" is thought to exist which indicates the bidirectional regulation mechanism between FASN and HER2.…”
Section: Metabolic Reprogramming In Breast Cancermentioning
confidence: 99%